Peran Zakat Dalam Mendukung Program Sustainable Development Goals Pada Baznas Kota Jambi - Pangiuk, Ambok; Dhiya An-Najwa, Semita (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
Zakat is an Islamic philanthropy and can be said to be one of the instruments that has a strategic role and contribution to the achievement of Sustainable Development Goals or sustainable development. The intersection between Sustainable Development Goals and zakat is united with the goal of poverty alleviation, including hunger in this world in various forms. Many ideas and concepts have emerged trying to connect one point of the Sustainable Development Goals with the definition of zakat, especially from the perspective of beneficiaries and the scope of zakat. Therefore, this study discusses how the implementation and role of zakat in supporting the Sustainable Development Goals program. The research method used is a qualitative research method. The results of the study show that the implementation of zakat carried out by BAZNAS Jambi City has been fully distributed to the mustahik through the implementation of the BAZNAS Jambi City work program. This indicates that zakat managed by BAZNAS Jambi City fully supports the Sustainable Development Goals program, as evidenced by the existence of superior programs from BAZNAS Jambi City. The programs distributed by BAZNAS Jambi City are Jambi Peduli, Jambi healthy city, Jambi clean city, Jambi pious city and independent Jambi. From the flagship programs of BAZNAS Jambi City, in the calculation of the overall SDGs index, it has a very good contribution value. In other words, the zakat distributed by BAZNAS Jambi City provides support for the Sustainable Development program in Jambi City, although the support is not yet significant.